2012
DOI: 10.2478/s11658-012-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of placenta extracts against nitrite-induced oxidative stress in human erythrocytes

Abstract: Aqueous-saline human placenta extract (HPE) is known to possess antioxidant activity due to the high concentration of bioactive substances. This fact allows its application in clinical practice in order to treat oxidation-induced diseases. Extract antioxidant activity is mainly conditioned by proteins. Freezing of extracts has been shown to lead to their antioxidant activity increasing due to protein conformation changes. Different biological models are widely used in order to evaluate efficacy of novel antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Pretreatment with hPH also reversed the extensive vacuolization, severe intrahepatic hemorrhage, destruction of nuclei, and loss of hepatic cords. Consistently, it has been reported that hPH possesses a variety of biological activities, including anti-inflammatory ( 26 , 52 56 ) and antioxidant ( 26 , 57 59 ) properties. Exposure to hazardous components from the environment can lead to pregnancy loss, uterine dysfunction, or fetal death ( 60 ).…”
Section: Discussionsupporting
confidence: 56%
“…Pretreatment with hPH also reversed the extensive vacuolization, severe intrahepatic hemorrhage, destruction of nuclei, and loss of hepatic cords. Consistently, it has been reported that hPH possesses a variety of biological activities, including anti-inflammatory ( 26 , 52 56 ) and antioxidant ( 26 , 57 59 ) properties. Exposure to hazardous components from the environment can lead to pregnancy loss, uterine dysfunction, or fetal death ( 60 ).…”
Section: Discussionsupporting
confidence: 56%
“…Several studies have revealed that placenta extract can inhibit fatigue, aging and many other diseases ( Biswas et al, 2001 ; Kong et al, 2008 ; Kong and Park, 2012 ; Rozanova et al, 2012 ). Placenta was also reported to have a possible anti-oxidant and immune-modulating effect in various biological systems ( Park et al, 2010 ; Kawakatsu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though fatigue decreases the quality of life in people there are only few pharmacological drugs or therapies available for the treatment of fatigue ( Fukuda et al, 1994 ; Kim et al, 2005 ; Reeves et al, 2007 ; Uthayathas et al, 2007 ). It has been showed that, placenta has protective effect on chronic fatigue, and many other diseases ( Biswas et al, 2001 ; Kong et al, 2008 ; Rozanova et al, 2012 ). Moreover, peptides protect mitochondrial viability, and minimize further ROS generation ( You et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported oxidative stress to be one of the mechanisms by which nitrite exerts its toxicity, under in vitro and in vivo conditions (Rozanova et al, 2012;Ansari et al, 2015;Jia et al, 2015). Chronic nitrite exposure may be associated with other health problems including respiratory tract diseases, neurological disorders, permanent growth inhibition, carcinogenesis and mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing risk of nitrite exposure necessitates the need to elucidate the biochemical mechanisms underlying the toxicity of nitrite salts and discover products, preferably from natural sources, which may protect against the harmful effects of nitrite. Several studies have reported oxidative stress to be one of the mechanisms by which nitrite exerts its toxicity, under in vitro and in vivo conditions (Rozanova et al, 2012;Ansari et al, 2015;Jia et al, 2015). Since carnosine (CAR) and N-acetyl cysteine (NAC) are reported to possess antioxidant properties, they may offer protection against nitrite-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%